Neonatal Feeding Trajectories in Mothers With Bipolar Disorder Taking Lithium: Pharmacokinetic Data - Imaz, Maria Luisa; Langohr, Klaus; Torra, Mercè; Soy, Dolors; García-Esteve, Luisa; Martin-Santos, Rocio (Frontiers in Pharmacology, 2021)
Purpose: Women who take lithium during pregnancy and continue after delivery may choose to breastfeed, formula feed, or mix these options. The aim of the study was to evaluate the neonatal lithium serum concentrations based on these three feeding trajectories. Methods: We followed 24 women with bipolar disorder treated with lithium monotherapy during late pregnancy and postpartum (8 per trajectory). Lithium serum concentrations were determined by an AVL 9180 electrolyte analyser with a 0.10 mEq/L detection limit and a 0.20 mEq/L limit of quantification (LoQ). Results: There was complete lithium placental passage at delivery, with a mean ratio of lithium concentration in the umbilical cord to maternal serum of 1.12 ± 0.17. The median times to LoQ were 6–8, 7–8, and 53–60 days for formula, mixed, and breast feeding respectively. The generalized logrank testing indicated that the median times to LoQ differ according to feeding trajectory (p=0.037). According to the multivariate analysis-adjusted lithium serum concentrations at birth, times to LoQ are, on average, longer under exclusive breastfeeding (formula, p=0.015; mixed, p=0.012). No lithium accumulation was observed in infants under either exclusive or mixed breastfeeding. During the lactation follow-up, there was no acute growth or developmental delays in any neonate or infant. Indeed, lithium concentrations in the three trajectories declined in all cases. However, the time needed to reach the LoQ was much longer for those breastfeeding exclusively. Conclusions: In breastfeed infant no sustained accumulation of lithium and no adverse effects on development or growth were observed.